Effect of Resistance Exercise Training Program on Quality of Life in Women with and without Polycystic Ovary Syndrome; A Cross Sectional Survey - Amara Saeed, Faryall Kemall, Javeria Iqbal, Romasa Sarwar, Maria Mustafa, Muhammad Tahir (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Polycystic ovary syndrome affects between 5% and 10% of reproductive-age women. Acanthosis nigricans is common in these patients and increases the risk of insulin resistance. These clinical symptoms could be detrimental to an individual’s self-esteem and quality of life. Objective: The objective of this study was to determine the effect of resistance exercise training program on the quality of life in females with and without polycystic ovarian syndrome. Methods: This was a non-randomized 8-week clinical trial, conducted from July 2021 to January 2022, in community women of reproductive age 18 to 45 taken as controls and women having polycystic ovarian syndrome enrolled at Link Medical Centre, Lahore. The inclusion criteria were women having polycystic ovarian syndrome, diagnosed using the Rotterdam Consensus, having amenorrhea or oligomenorrhea, biochemical and/or clinical evidence of polycystic ovaries or hyperandrogenism found by pelvic ultrasonography. The research analysed 79 polycystic ovarian syndrome women and 64 healthy women. polycystic ovarian syndrome and healthy control groups were tested at baseline and after the 8-week RET. The data was analysed in SPSS 25.0. Results: The results regarding quality of life, it was seen that in PCOS the domains of quality of life that improved significantly from baseline, week 0 to week 8 were found to be functional status (baseline M±SD, 87.23 ± 13.27; week 8 M±SD, 91.64 ± 12.13), physical aspects (baseline M±SD, 76.24 ± 28.12; week 8 M±SD, 84.03 ± 28.38), pain (baseline M±SD, 67.13 ± 24.16; week 8 M±SD, 75.12 ± 21.31) and energy (baseline M±SD, 60.01 ± 16.78; week 8 M±SD, 64.52 ± 20.22) p value < 0.05, while to rest of domain did not improve including emotional, social, mental and general health status. (p value > 0.05). The results regarding quality of life, it was seen that in control group the domains of quality of life that improved significantly from baseline, week 0 to week 8 were found to be social aspects (baseline M±SD, 74.81 ± 25.34; week 8 M±SD, 84.21 ± 15.1), energy (baseline M±SD, 66.12 ± 20.13; week 8 M±SD, 75.41 ± 21.12) and mental health (baseline M±SD, 69.3 ± 21.34; week 8 M±SD, 78.14 ± 13.87) p value < 0.05, while to rest of domain did not improve including emotional, social, mental and general health status. (p value > 0.05). Conclusion: It was concluded based on the findings from an eight-week trial that women with PCOS benefited from resistance exercise training program various SF-36 quality of life domains including function, physical aspects, pain, and energy while the control group benefited from exercise in domains related to psychological wellbeing such as emotional function, energy, and socialization. Resistance exercise training can be employed as effective therapeutic remedy for improving quality of life in women health issues such as PCOS. On the other hand, exercise is equally effective in women without any health issue and help boost quality of life in psychosocial aspects. Keywords: Quality of Life, Polycystic Ovarian Syndrome, Healthy Women, Resistance Exercise Training